2016
DOI: 10.1016/j.expthermflusci.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The flow field structure of highly stabilized partially premixed flames in a concentric flow conical nozzle burner with coflow

Abstract: The flow field structure of highly stabilized partially premixed flames in a concentric flow conical nozzle burner with coflow KAUST Repository a b s t r a c tThe stability limits, the stabilization mechanism, and the flow field structure of highly stabilized partially premixed methane flames in a concentric flow conical nozzle burner with air co-flow have been investigated and presented in this work. The stability map of partial premixed flames illustrates that the flames are stable between two extinction li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…They [15] found that the existence of the air coflow improves the flame stabilization. However the flame structure, the mixing field, and flame/flow field interaction were not investigated in their work.…”
Section: Flame Stability and Selected Flamesmentioning
confidence: 99%
See 3 more Smart Citations
“…They [15] found that the existence of the air coflow improves the flame stabilization. However the flame structure, the mixing field, and flame/flow field interaction were not investigated in their work.…”
Section: Flame Stability and Selected Flamesmentioning
confidence: 99%
“…The range of the mixture fraction fluctuations plays a crucial rule in the flame stabilization mechanism. Recently, the effect of the air coflow velocity on the stability of methane partially flames stabilized in CFCN burner was investigated by Elbaz et al [15].…”
Section: Flame Stability and Selected Flamesmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics and structures of partially premixed flames have been studied by means of advanced laser-based optical measurement techniques (Barlow et al, 2017;Elbaz et al, 2018Elbaz et al, , 2016El-Mahallawy et al, 2007;Li et al, 2009;Mansour et al, 1989;Mansour 70 et al, 2017a;Mansour et al, 2012;Meares et al, 2015;Meares and Masri, 2014;Yan et al, 2010) and experimental data were used to analyze the dependences of the degree of premixing (Meares et al, 2015;Meares and Masri, 2014) and the impact of different fuel compositions on flame stability (Yan et al, 2010). Lasers have been applied for example for Rayleigh/Raman measurements to determine local temperature and gas 75 composition in flames (Barlow et al, 2009;Brands et al, 2014;Cheng et al, 2012;Fuest et al, 2011Fuest et al, , 2015Fuest et al, , 2012Mansour et al, 1999;Mansour and Yung-Cheng, 1996;Raffius et al, 2017;Wehrmeyer et al, 1992).…”
Section: Q5mentioning
confidence: 99%